Detection and characterization of simvastatin and its metabolites in rat tissues and biological fluids using MALDI high resolution mass spectrometry approach - Wencui Yin; Reem I. Al-Wabli; Mohamed W. Attwa; A. F. M. Motiur Rahman; Adnan A. Kadi (Scientific Reports, 2022)
Abstract Simvastatin (SV) is a hypolipidemic agent, and it is the 2nd most widely prescribed lipid-lowering drug. Here, the detection and characterization of SV and its metabolites was studied in selected organs/tissues (lung, liver, brain, heart and kidney) and biological samples (blood, urine and feces) of rats. MALDI Orbitrap MS was used as a high-resolution mass analyzer. 2,5-Dihydroxybenzoic acid (DHB) and 1,5-diaminonaphthalene (DAN) were used as matrices. Several sample loading methods onto the MALDI plate were attempted and dried droplet method was found to be superior. Two different cell disruption methods, pulverization and homogenization, were also evaluated for the optimum sensitivity in MALDI. Pulverization allowed the detection of more metabolites in all organs except the liver, where homogenization led to the detection of more metabolites. Altogether, 13 metabolites were detected, and one metabolite tentatively identified as a reduced product is being reported for the first time. SV and its metabolites were distributed to all the tissues studied except the brain. Overall, the results implied that the pulverized samples were more uniform and larger in surface area, resulting in their more efficient and complete extraction during sample preparation. As shown in the present study, MALDI Orbitrap MS is a useful tool to study drug and metabolite detection and characterization.